Scapula Mobilization For Improving Functional Ability In Frozen Shoulder Conditions: Case Study - Nugraha, Fitria Maharani; Pristianto, Arif; Zakaria, Ricky Fauzi (Universitas Muhammadiyah Surakarta, 2023)
Background: Frozen Shoulder is characterized by progressive pain resulting in stiffness and limited active and passive motion in the shoulder joint. The primary or idiopathic cause of frozen shoulder is not known with certainty, while secondary causes are usually due to trauma, thyroid disease, and rheumatoid arthritis. Objective: This study aims to determine the effect of scapula mobilization to improve functional ability in frozen shoulder conditions. Method: This study used the case study method which was conducted on frozen shoulder patients at Condong Catur Hospital Yogyakarta in November 2022. Shoulder Pain and Disability Index (SPADI) to measure functional ability. SPADI is a quality of life questionnaire consisting of 13 items to evaluate 5 items for pain and 8 items for disability. Results: After 3 times of physiotherapy, the results showed reduced pain, increased muscle strength, increased ROM, and increased functional ability. Conclusion: Scapula mobilization is effective in reducing pain, increasing muscle strength, and increasing ROM so that there is also an increase in functional ability.